Preparation and electrochemical properties of polyaniline/α‐RuCl3.xH2O composites for supercapacitor. Issue 12 (15th August 2013) - He, Benlin; Meng, Xin; Zhu, Yongbo; Tang, Qunwei
<x xml:space="preserve">Abstract</x> Polyaniline/α‐RuCl3.xH2O composites were successfully synthesized by an in‐situ chemical polymerization and employed as new electrode materials in supercapacitors. The synthesized composites were characterized physically by scanning electronic microscope (SEM). The electrochemical capacitance performance of these composites was investigated by cyclic voltammetry, galvanostatic charge–discharge tests and AC impedance spectroscopy with a three‐electrode system in 1 mol l−1 NaNO3 aqueous solution electrolyte. The polyaniline/α‐RuCl3.xH2O composites electrodes showed much higher specific capacitance, better power characteristics and were more promising for application in capacitor than pure polyaniline electrode. The effect and role of α‐RuCl3.xH2O in the composite electrode were also discussed in detail. POLYM. COMPOS., 34:2142–2147, 2013. © 2013 Society of Plastics Engineers